New soft masculinity discourse in era digital: A critical analysis of Zayn Malik’s Instagram posts - Jessica Debora Tibefrilia; Euis Meinawati (English Learning Innovation, 2026)
This research explores how soft masculinity is portrayed in seven Instagram posts by Zayn Malik from 2024 to 2025, using Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA) model. The analysis occurred between April and October 2025. Employing a qualitative method, the study used Critical Discourse Analysis (CDA) grounded in Fairclough's model. Data gathering involved recording posts, encompassing images, text, and user engagements. Analytical methods encompassed textual and multimodal scrutiny across micro, meso, and macro scales, along with an assessment of discursive and broader social practices. Findings reveal that Zayn primarily embodies soft masculinity through casual and personal visual stances, affectionate and exposed facial cues, and language conveying appreciation, emotional honesty, modesty, and interpersonal compassion. These traits blend with lingering traditional masculine symbols (such as leather jackets, tattoos, and beards), resulting in a blended yet clearly soft form of masculinity that opposes dominant norms of control, emotional restraint, and detachment. The study argues that Zayn Malik's recent Instagram content represents a sincere challenge to traditional masculine ideals, rather than superficial or profit-oriented weakness, thus enriching modern perspectives on inclusive masculinity within online celebrity spheres.